2016
DOI: 10.5483/bmbrep.2016.49.10.057
|View full text |Cite
|
Sign up to set email alerts
|

ASIC2a-dependent increase of ASIC3 surface expression enhances the sustained component of the currents

Abstract: Acid-sensing ion channels (ASICs) are proton-gated cation channels widely expressed in the nervous system. Proton sensing by ASICs has been known to mediate pain, mechanosensation, taste transduction, learning and memory, and fear. In this study, we investigated the differential subcellular localization of ASIC2a and ASIC3 in heterologous expression systems. While ASIC2a targeted the cell surface itself, ASIC3 was mostly accumulated in the ER with partial expression in the plasma membrane. However, when ASIC3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
2
2
0
Order By: Relevance
“…We also investigated the ability of mASIC3 and nmrASIC3 to form heteromers with rASIC2a and found that as shown previously ( 7 , 43 ) coexpression of mASIC3 and rASIC2a resulted in currents with an I sus / I peak that was significantly greater than that produced by either mASIC3 or rASIC2a homomers (mASIC3 + rASIC2a: 141 ± 25, n = 13 versus mASIC3: 48 ± 4%, n = 23, p < 0.001 and rASIC2a 29 ± 6%, n = 8, p < 0.001, Fig. 4 , A and D ).…”
Section: Resultssupporting
confidence: 73%
“…We also investigated the ability of mASIC3 and nmrASIC3 to form heteromers with rASIC2a and found that as shown previously ( 7 , 43 ) coexpression of mASIC3 and rASIC2a resulted in currents with an I sus / I peak that was significantly greater than that produced by either mASIC3 or rASIC2a homomers (mASIC3 + rASIC2a: 141 ± 25, n = 13 versus mASIC3: 48 ± 4%, n = 23, p < 0.001 and rASIC2a 29 ± 6%, n = 8, p < 0.001, Fig. 4 , A and D ).…”
Section: Resultssupporting
confidence: 73%
“…We also investigated the ability of mASIC3 and nmrASIC3 to form heteromers with rASIC2a and found that as shown previously (7,43) coexpression of mASIC3 and rASIC2a resulted in currents with an I sus /I peak that was significantly greater than that produced by either mASIC3 or rASIC2a homomers (mASIC3+rASIC2a: 141 ± 25, n = 13 vs. mASIC3: 48 ± 4 %, n = 23, p < 0.001 and rASIC2a 29 ± 6 %, n = 8, p < 0.001 Fig. 4A and D).…”
Section: Nmrasic3 Forms Functional Asic Heteromers With Other Asic Susupporting
confidence: 66%
“…ASIC3 is mainly located in the peripheral dorsal root ganglion (DRG) neurons [ 4 , 42 ]. Other locations of ASIC3 in the PNS include the spiral ganglia, nodose ganglia, trigeminal ganglia, and neurons in the bladder [ 43 ]. In addition to forming functional channels with other ASIC subunits, such as ASIC1a [ 44 ], ASIC3 is also associated with the P2X3 ion channel [ 45 ].…”
Section: Introductionmentioning
confidence: 99%